Manajemen Risiko Metode Pembayaran Cash on Delivery Shopee E-Commerce - Maryam Batubara; Abdurrozzaq Ismail; Luthfiah Nazmi (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Abstract Cash On Delivery is one of the payment methods provided to customers by online marketplace companies. However, various problems emerged along with the incessant promotion of shopping using the Cash On Delivery payment method. This research was conducted using a descriptive method with a qualitative approach based on data sources from literature studies and observations. The aim of this research is to provide an overview of the risks regarding the Cash On Delivery payment method from the online seller's side and analyze Shopee's policy on handling risks related to the Cash On Delivery payment method. The research results show that the factors behind unilateral cancellation of transactions result in loss of energy, risk of financial loss, risk of loss of time and risk of decreased store performance. Shopee has implemented several policies aimed at minimizing risk, but Shopee must be able to make the pay on delivery feature even better. Considering that unilateral cancellations from customers are very detrimental to the seller. Keywords: Cash On Delivery, Risk Management, Payment Methods